Combined analysis of multi-omics reveals the potential mechanism of flower color and aroma formation in Macadamia integrifolia - Wang, Yonggui; Xia, Jing; Wang, Zile; Ying, Zhiping; Xiong, Zhi; Wang, Changming; Shi, Rui (Frontiers in Plant Science, 2023)
Macadamia integrifolia Maiden & Betche is a domesticated high-value nut crop. The development of nut flower affects the fruit setting rate, yield and quality of nuts. Therefore, in this experiment, two varieties with different flower color, flowering time, flowering quantity and nut yield (single fruit weight) were selected as the research objects. Transcriptome (RNA-Seq) and metabolome (LC-MS/MS, GC-MS) analyses were performed to study the regulatory mechanisms of nut flower development, color and aroma. The results indicated that plant hormone signal transduction, starch sucrose metabolism, phenylpropanoid metabolism, flavonoid biosynthesis, and anthocyanin biosynthesis pathways were related to nut flower development and flower color formation. In the early stage of flowering, most of the differentially expressed genes (DEGs) are involved in the IAA signal transduction pathway, while in the later stage, the brassinolide signal pathway is mainly involved. In starch and sugar metabolism, DEGs are mainly involved in regulating and hydrolyzing stored starch into small molecular sugars in flower tissues. In the phenylpropanoid biosynthesis pathway, DEGs are mainly related to the color and aroma (volatile organic compounds, VOCs) formation of nut flowers. Four color formation metabolites (anthocyanins) in nut flowers were found by LC-MS/MS detection. In addition, the VOCs showed no significant difference between red nut flowers (R) and white nut flowers (W), which was mainly reflected in the aroma formation stage (flowering time). And 12 common differentially accumulation metabolites (DAMs) were detected by GC-MS and LC-MS/MS. At the same time, the DEGs, AAT, LOX and PAL genes, were also identified to regulate key metabolite synthesis during nut flower development. These genes were further verified by qRT-PCR. Our results provide insights to clarify the molecular mechanism of color and aroma formation during M. integrifolia flower development that pave the way for nut quality and yield breeding.